Palynological study of some species in Grumorsae group of the genus Ranunculus in Iran - Maneezheh Pakravan; Anahita Jamshid nejad Avval; Akhtar Tavassoli (تاکسونومی و بیوسیستماتیک, 2014)
In this research, pollen grains of some species of Grumorsae group of Ranunculus were studied. In doing so, pollen grains of 13 species were studied by light microscope and the surface of nine pollen grains has studied by Scanning Electron Microscope. Among these species, in addition to previous pollen types in the genus Ranunculus, a new type (Thalictrum flavum L.) was reported. Finally, we could distinguish the species based on pollen grains characters and prepare an identification key.